The lexical domain of 'fauna' in John Florio's A Worlde of Wordes and Shakespeare's plays: sociocultural implications - Blas, V (2010)
This paper deals with John Florio's A Worlde of Wordes (1598). This Italian-English dictionary represents a major innovation within the history of English lexicography, in the sense that while previous works were glossaries of hard words for Latin or Greek, Florio's dictionary is the first great work that translates terms from Italian into English. The case of William Shakespeare, who owes much of his comprehensive knowledge of Italian culture to his alleged friend John Florio, is the epitome of this contact between two coetaneous worlds and their languages. The underlying premise in this avenue of research is that a dictionary should be seens as a valuable sample of materials in the form of definitions that can be used to describe a particular culture. Accordingly, in this work I attempt to determine to what extent the publication of A Worlde of Wordes and Queen Anna's New World of Words enriched the lexis of the 17th-century English literary panorama and the sociocultural implications of this process. Florio's overall contribution to English language has been quantified in more than a thousand terms. However, a detailed analysis of the definitions in his dictionary is still missing. In this proposal, the cognitive field of 'fauna', the topic has been approached from the Prototype Theory in order to build up the lexical cultural frame of fauna in John Florio's time. A comparison between the lexical entries dealing with animals and the contexts in which they are used in Shakespearean plays has revealed that the degree of knowledge of animals is determined by certain social and cultural factors. In this sense, an exhaustive description of the definitions selected has been useful to obtain information about the English Renaissance - despite the vast amount of work on Shakespeare's works and time.